The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.14746/ssllt.2018.8.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Classroom anxiety and enjoyment in CLIL and non-CLIL: Does the target language matter?

Abstract: This study investigates pupils' anxiety and enjoyment in the classroom when learning a second or foreign language. The particularity of this study lies in the comparison of two target languages (English and Dutch) in two educational contexts (CLIL and non-CLIL) at different instruction levels (primary and secondary education). While most research on content and language integrated learning (CLIL) focuses on English as a target language, the Belgian context calls for a comparison with the language of the "other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 37 publications
2
65
1
2
Order By: Relevance
“…Additionally, in the present study, in a negative CE, the impact of grit on FLE was not significant. Previous studies have found that students’ academic emotion is largely influenced by the CE; for instance, in a negative CE, even students with a high level of grit cannot enjoy their studies (De Smet et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the present study, in a negative CE, the impact of grit on FLE was not significant. Previous studies have found that students’ academic emotion is largely influenced by the CE; for instance, in a negative CE, even students with a high level of grit cannot enjoy their studies (De Smet et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of political and historical context and the effect of the target language were at the heart of the investigation of De Smet et al (2018) on the FLE and FLCA of 896 Belgian francophone primary and secondary school pupils. They compared two target languages (English and Dutch) in two different types of school in francophone parts of Belgium.…”
Section: Positive Psychology In Applied Linguisticsmentioning
confidence: 99%
“…It depends on interactions with peers, teachers, classroom activities and is influenced by a more general societal, historical and political context (Dewaele and MacIntyre 2014). Learners have been found to experience more negative emotions and less enjoyment in classes where the FL was associated with a community with which political relations were strained (De Smet al 2018). Enjoyment is also a strong predictor of willingness to communicate (WTC) in the FL class (Dewaele 2019b;Khajavy et al 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Foreign Language Enjoyment (FLE) and Foreign Language Classroom Anxiety (FLCA) have been found to have complex dynamic relationships with both learner-internal and contextual variables (Dewaele and Dewaele 2017; Dewaele and MacIntyre 2014, 2016Karci, Özdemir and Balta 2018) and play an important part in learners' Willingness to Communicate in the Foreign Language (FL) and in their performance in the FL . Relationships have been found to be broadly similar in FL classes in different parts of the world, including Belgium (De Smet et al 2018), China (Jin and Zhang 2018, Li 2018Li, Jiang and Dewaele 2018;Li, Dewaele and Jiang, 2019); Iran (Shirvan and Taherian 2018; Shirvan and Talebzadeh 2018); Japan (Saito et al 2018); Poland (Piechurska-Kuciel 2017), Saudi Arabia (Dewaele and Alfawzan 2018), Spain (Dewaele, Magdalena Franco and Saito 2019) and the United Kingdom (Dewaele and Dewaele 2017;Dewaele, Witney, Saito and Dewaele 2018). Most of these studies focused on English as a FL.…”
Section: Introductionmentioning
confidence: 99%